Impact of feed quality on animal health and food safety - Bengoumi M.; Boulajfene H. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The livestock sector accounts for 40% of the global value of agricultural production and enhances the livelihoods and food security of nearly 1.3 billion people in the world. Animal feed accounts for about 79% of global vegetable protein consumption (including fodder) and 58% of protein concentrates (FAOStat, 2017). Animal feed is an important source of hazards to the human food chain, its safety must be assessed prior to its feeding to animals. Feed safety includes the impact on human as well as animal health and welfare, which, in turn, can affect productivity. Safety assessments are often multifaceted. The range of potential hazards associated with feed is broad and possibly increasing with the rising importance of different feed sources and feed production technologies. The main chemical hazards are persistent organic pollutants, veterinary drug residues, organochlorine and other pesticides, potentially toxic elements, mycotoxins, plant toxins, etc. Biological hazards are mainly bacterial, viral, parasitic, fungal pathogens and prions. While physical hazards include nanomaterials and radionuclides. Feed safety assessment is costly and needs highly qualified laboratories. Therefore, risk assessment, risk management and risk communication are key elements for ensuring feed safety. FAO, WHO and OIE have developed international standards for feed safety and established the ad hoc Codex Intergovernmental Task Force on Animal Feeding. FAO and WHO provide the scientific basis to Codex through the Joint FAO/WHO Expert Committee on Food Additives (JECFA); the Joint FAO/WHO Meetings on Pesticide Residues (JMPR), the Joint Expert Meetings on Microbiological Risk Assessment (JEMRA) and the Joint FAO/WHO ad hoc Expert Meetings on Safety Assessment of Food Derived from Biotechnology. FAO has developed a series of programmes to support member countries in ensuring feed safety including compilation and dissemination of information, promotion of wide alliances and partnership with the private sector, technical assistance and capacity– and institutional building; and awareness raising and policy advice.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)